Adsorption of Polyvinylpyrrolidone and its Impact on Maintenance of Aqueous Supersaturation of Indomethacin via Crystal Growth Inhibition. Issue 9 (2nd June 2015) - Patel, Dhaval D.; Anderson, Bradley D.; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> This study explored the adsorption and crystal growth inhibitory effects of polyvinylpyrrolidone (PVP) on indomethacin crystals in an aqueous medium. A solution depletion method was used to construct adsorption isotherms of PVPs with different molecular weights and N‐vinylpyrrolidone onto indomethacin crystals. The affinity for and extent of maximum adsorption of PVP on indomethacin crystals were significantly higher than that of N‐vinylpyrrolidone, which was attributed to cooperative interactions between PVP and the surface of indomethacin. The extent of PVP adsorption onto indomethacin crystals in terms of mg/m2 was greater for higher molecular weight PVP but less on a molar basis indicating an increased percentage of loops and tails for the higher molecular weight PVP. PVP significantly inhibited the crystal growth of indomethacin at a high degree of supersaturation as compared with N‐vinylpyrrolidone, which was attributed to a change in indomethacin crystal growth mechanism leading to a change in the rate limiting step from bulk diffusion to surface integration. Higher molecular weight PVPs are better inhibitors of the crystal growth of indomethacin than lower molecular weight PVPs, which was attributed in part to a greater barrier for surface diffusion of indomethacin provided by a thicker adsorption layer of PVP. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2923–2933, 2015